Comparison of the effect of "knee-ankle-foot" orthosis with orthosis "progressive linkage media" on gait performance and energy consumption in a patient with spinal cord injury Thoracic level: Case report - Seyyedzadeh, Hanieh; Razeghinezhad, Reza; Daryabor, Aliyeh; Arazpour, Mokhtar (Journal of Clinical Physiotherapy Research, 2020)
.